PELATIHAN DESAIN GRAFIS MENGGUNAKAN ADOBE PHOTOSHOP UNTUK MEMBUAT PAMFLETPADA MURID SMK AL-KARIMAH - efendi, Budiman; Ahmad Tantoni (Jurnal Pekayunan, 2025)
AbstractIn today's increasingly advanced digital era, the utilization of graphic design has become an essential skill, particularly in supporting promotional activities, social campaigns, and digital education. This community service activity aims to provide training on creating pamphlets for students of SMK Al Karimah, organized by fourth-semester students of STMIK Lombok who are currently undergoing fieldwork practice.The training method used was demonstration and hands-on practice utilizing Adobe Photoshop as the design tool and pamphlets as the publication platform, with a creative practice-based approach. The implementation of the training included material presentation sessions, demonstrations on pamphlet creation, and independent practice guided by tutors.The results of this activity showed a significant improvement in participants' understanding and skills, as evidenced by the comparison between pre-test and post-test scores.Challenges encountered included a shortage of devices/laptops, which led one participant to use their own mobile phone, causing difficulties during the hands-on and independent practice sessions. Despite this, the training successfully enhanced participants’ digital literacy and broadened their awareness of the importance of graphic design in supporting various activities in the modern era.